Copepod secondary production in the sea: Errors due to uneven molting and growth patterns and incidence of carcasses. (July 2018) - Yáñez, Sonia; Hidalgo, Pamela; Ruz, Paula; Tang, Kam W.
Highlights: Errors in secondary production estimation were observed in the dominant copepods. P . cf. indicus being more sensitive to inclusion of carcasses. The error was not evenly distributed across the months in all three species. The errors also varied in magnitude and in sign among developmental stages. Abstract: Secondary production of copepods is one of the basic parameters that govern the structure and function of the marine pelagic food web, and it is commonly estimated as cumulative biomass increase through consecutive molting based on short-term molting rate (MR) incubation experiments. The accuracy of the method depends on two underlying assumptions: (1) Even stage duration and inter-molt growth; (2) All copepods in situ are alive. We conducted a year-long study in a coastal bay within the Humboldt Current System to assess the errors in copepod secondary production estimation when these assumptions are violated. Abundances of live and dead individuals of the dominant species: Paracalanus cf. indicus, Acartia tonsa and Calanus chilensis were measured monthly. Concurrent molting rate experiments were conducted to derive copepod secondary production. A modified MR formulation was used to correct the secondary production estimates for error in assumption (1), and the live/dead copepod data were used to correct the estimates for error in assumption (2). Violation of the underlying assumptions caused error in secondary production estimation, most severely in P. cf. indicus . The error was not evenly distributed across the months, and in the case of C. chilensis, it switched between over- and under-estimation repeatedly. The annual average error was −39.2% in P. cf. indicus, 3.1% in A. tonsa, and 5.2% in C. chilensis . The errors also varied in magnitude and in sign among developmental stages, with some stages yielding nearly 70% over-estimation. For copepod species with short generation times, even small errors could quickly propagate and result in highly skewed secondary production projection. Reliable secondary production measurements therefore require careful assessment of species-specific stage duration and between-stage growth when applying the MR method, and quantification of stage-specific live and dead individuals in the field.